ANALISIS STRATEGI PENGEMBANGAN PRODUK PADA BATIK SEMARANG 16 - Indah Fajar Cahyati; Nawazirul Lubis; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2015)
Product development is one thing that is important and should be done by a business that sells a product that can be accepted by consumers. This study aims to determine the strategy of product development at Batik Semarang 16 and determine the impact of internal and external factors that encourage the development of products. Methods of data collection using interviews and observation. Key informants in this study were employees of Batik Semarang 16. This study used qualitative analysis techniques.The survey results revealed that the product development strategy conducted by Batik Semarang 16 is to develop a design motif of products and also adding new product lines. Jug external factors play a role in encouraging the development of more effective products